2019
DOI: 10.1161/hypertensionaha.119.13285
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 (Transient Receptor Potential Vanilloid 1) Cardiac Spinal Afferents Contribute to Hypertension in Spontaneous Hypertensive Rat

Abstract: Hypertension is associated with increased sympathetic activity. A component of this sympathoexcitation may be driven by increased signaling from sensory endings from the heart to the autonomic control areas in the brain. This pathway mediates the so-called cardiac sympathetic afferent reflex, which is also activated by coronary ischemia or other nociceptive stimuli in the heart. The cardiac sympathetic afferent reflex has been shown to be enhanced in the heart failure state and in renal hypertension. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Studies employing cardiac afferent ablation in hypertensive animals coupled with measurement of venous tone will be needed to answer this question. Recent work is consistent with this possibility since ablation of cardiac sensory afferents attenuated hypertension development in the SHR (Shanks et al, 2019), a model in which elevation in venous tone and cardiac output are associated with hypertension development.…”
Section: Fig 3 Ventricular Bradykinin Receptor Expressionmentioning
confidence: 58%
See 1 more Smart Citation
“…Studies employing cardiac afferent ablation in hypertensive animals coupled with measurement of venous tone will be needed to answer this question. Recent work is consistent with this possibility since ablation of cardiac sensory afferents attenuated hypertension development in the SHR (Shanks et al, 2019), a model in which elevation in venous tone and cardiac output are associated with hypertension development.…”
Section: Fig 3 Ventricular Bradykinin Receptor Expressionmentioning
confidence: 58%
“…Collectively, we believe that these data show that pericardial injection of bradykinin causes systemic venoconstriction sufficient to participate in the overall cardiovascular response to activation of the CSAR. Convincing data show that activity of the CSAR is enhanced in the settings of heart failure (Wang et al, 2017;Wang et al, 2014) and hypertension (Chen et al, 2015;Shanks et al, 2019). Venous tone is increased in heart failure (Nekooeian and Pang, 2000) and in hypertension (Fink and Arthur, 2009;Martin et al, 1998;Fink et al, 2000).…”
Section: Fig 3 Ventricular Bradykinin Receptor Expressionmentioning
confidence: 99%
“…For example, it has been demonstrated recently that desensitization of TPRV1 in cardiac afferent neurons by resiniferatoxin exhibits protective effects against autonomic dysfunction in heart failure animals (124,125). Furthermore, ablation of cardiac afferent nerves by resiniferatoxin at the level of the upper thoracic DRG can prevent the development of hypertension in spontaneously hypertensive rats (126). We previously demonstrated that blockade of TRPV1, which contributes significantly to EPR activation (73), significantly reduced pressor and sympathetic responses to suprastimulation of the metaboreflex (via ischemic hindlimb muscle contraction) in spontaneously hypertensive rats (60).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Previous research has shown that members of the TRP family closely relate to cardiovascular disease ( Ma et al, 2017 ). TRPV1 channel can regulate vascular smooth muscle and improve hypertension, causing heart dysfunction under cold exposure ( Zhang et al, 2012 ; Shanks et al, 2019 ). The TRPV1 and TRPV4 channels are involved in the cardiovascular protection of hypoxia.…”
Section: Introductionmentioning
confidence: 99%